The interplay mechanisms between gut microbiota and ferroptosis in inflammatory bowel disease - Shi, Zihan; Zhang, Shuyun; Zhai, Hongru; Wu, Qingmin; Li, Yanyun; Xu, Huibin; Zhang, Shanlong (Frontiers in Immunology, 2026)
Inflammatory bowel disease (IBD) is a chronic relapsing disorder driven by complex interactions between genetic susceptibility, immune dysregulation, and environmental factors. Ferroptosis has been identified as a key regulator in the progression of IBD. While much research focuses on endogenous signaling pathways, extrinsic mechanisms—particularly the modulation of IBD through the gut microbiota-induced ferroptosis remain underexplored. Dysregulated ferroptosis, influenced by gut microbiota, exacerbates microbial imbalance, creating a vicious cycle. Notably, the gut microbiota plays a critical role in IBD progression through multidimensional mechanisms, including regulation of metabolites, maintenance of immune homeostasis, and protection of the intestinal barrier. This review examines the microbiota–ferroptosis axis in IBD pathogenesis, aiming to provide insights into potential therapeutic strategies. In particular, we discuss emerging treatments targeting ferroptosis inhibition, iron homeostasis regulation, and microbiota interventions, which hold promise for improving clinical outcomes and promoting pathological recovery in IBD patients.